Case Report: Button battery ingestion—an underestimated emergency in children - Konzett, Karin; Gang, Stefanie; Poyntner, Lukas; Reithmeier, Eberhard; Dertinger, Susanne; Simma, Burkhard (Frontiers in Pediatrics, 2025)
In general, the battery-related emergency department visit rate has continued to rise in the last decade. We present two cases of previously healthy toddlers (14 and 24 months old) with unwitnessed battery ingestion, who presented with massive, hematocrit-relevant hematemesis. Initially, both children showed stable vital signs. Following a symptom-free interval, both had a recurrence of massive hematemesis, which could not be controlled despite a multidisciplinary approach with pediatric, radiology, ENT specialists, endoscopy and anesthesia. Pathological workup showed necrosis with secondary aortoesophageal fistula due to battery-induced colliquation necrosis caused by caustic soda produced at the minus pole. We conclude, that preclinical risk scores, excellent clinical pathways (e.g. from Children’s Hospital of Philadelphia) and detailed approaches from the National Capital Poison Center in the USA and also the European Society of Pediatric Gastroenterology Hepatology and Nutrition (ESPGHAN) offer clear and concise instructions for the management of button battery ingestion, but clinical awareness for vascular complications must be heightened. A multidisciplinary treatment algorithm for this fatal complication should be implemented and trained in pertinent hospitals. Moreover, it is of great importance to raise awareness for button battery ingestion in educational campaigns for parents and caregivers.